Don DeLillo, The Angel Esmeralda. Nine Stories (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2012)
Review of DeLillo, Don. The Angel Esmeralda. Nine Stories. New York: Scribner, 2011. Print.